2007
DOI: 10.1057/palgrave.jphp.3200126
|View full text |Cite
|
Sign up to set email alerts
|

An End to Perinatal HIV: Success in the US Requires Ongoing and Innovative Efforts that Should Expand Globally

Abstract: The dramatic reduction of perinatally transmitted HIV in the United States has been a striking success story in the HIV epidemic. Routine HIV screening during pregnancy followed by appropriate therapy has been extremely effective. This paper puts forth three strategies needed to maintain these gains and reach the goal of eliminating perinatal HIV: standardize medical interventions and policy changes that support perinatal HIV reduction; institute HIV screening in routine preconception care to identify HIV infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…Kesho Bora [22] reported 42.6% of the participants receiving <6 wk of triple ARVs antepartum and a transmission rate of 3.3%. Given these findings and the transmission rates below 2% in countries where triple-ARV prophylaxis is initiated during the second trimester and where breastfeeding is avoided [25], it is likely that initiating ARVs earlier during pregnancy in this study would have further reduced in utero and intrapartum transmission However, timely initiation of ARVs may be a challenge in areas where many women present late for antenatal care. A 2002 study of recently delivered women in rural western Kenya showed that 64% first visited the antenatal clinic in the third trimester [26].…”
Section: Discussionmentioning
confidence: 91%
“…Kesho Bora [22] reported 42.6% of the participants receiving <6 wk of triple ARVs antepartum and a transmission rate of 3.3%. Given these findings and the transmission rates below 2% in countries where triple-ARV prophylaxis is initiated during the second trimester and where breastfeeding is avoided [25], it is likely that initiating ARVs earlier during pregnancy in this study would have further reduced in utero and intrapartum transmission However, timely initiation of ARVs may be a challenge in areas where many women present late for antenatal care. A 2002 study of recently delivered women in rural western Kenya showed that 64% first visited the antenatal clinic in the third trimester [26].…”
Section: Discussionmentioning
confidence: 91%
“…Over 90% of these infections occur through mother-to-child transmission (MTCT) 4 . It is pertinent to note that without interventions, the rate of HIV MTCT ranges from 25% to 40%, however with effective interventions, HIV MTCT rates have been reduced below 2% 4 and virtually eliminated in most developed countries, while many developing countries including Nigeria, still record high pediatrics HIV transmission rates [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…23 HIV MTCT is high in sub-Saharan Africa, with rates as high as 25-40% without intervention. 23 The rate of MTCT has been reduced significantly in industrialised countries due to the implementation of prevention strategies, 24 and such strategies need to be vigorously pursued in Nigeria and other African countries to reduce the burden of HIV among children, and particularly infants.…”
Section: Discussionmentioning
confidence: 99%